Pelatihan Inovasi Trichokompos Limbah Kulit Kopi (TRICHOLIKO) Berbasis Agropreneurship bagi Petani Muda Enrekang - Nurhapisah, Nurhapisah; Suhardi, Suhardi; Baharuddin, Baharuddin; Akbar, Muh. Rezky; Suharman, Suharman (Jurnal Pengabdian UNDIKMA, 2024)
This community service programme aims to increase the knowledge and skills of young farmers in Enrekang in processing Trichocompost from coffee skin waste (Tricholiko) as organic fertilizer. The programme involved the Tunas Muda Kreatif Farmer Group located in Salowo Hamlet, Curio Village, Curio Sub-district, Enrekang Regency, South Sulawesi. Although the group already had products such as plant seeds, Sinar Benteng Arabica coffee, and Trichokompos, they faced various challenges in business development, including: a) lack of socialization on the use of Tricholiko in coffee and pepper intercropping systems, b) absence of demo plots to test the effectiveness of Trichokompos on pepper plants, and c) limited knowledge and skills in entrepreneurial management innovation and product marketing. The methods used in this programme included training and mentoring in the Trichokompos production process, with stages including: 1) entrepreneurship training and workshop, 2) training on Trichoderma sp. propagation and Tricholiko production, 3) making demo plot of Trichocompost application, and 4) assistance in product packaging. Evaluation was conducted using pre-test and post-test questionnaires and direct observation in the process of making Trichocompost. Data were analyzed descriptively to assess the improvement of knowledge and skills. The results of the service showed a significant increase in the knowledge and skills of young farmers in the production of Trichocompost, as well as an increase in partner independence in producing Tricholiko with greater yield and quality than before.